2011
DOI: 10.1021/jp202057q
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Control in Nanodiamond Produced by Detonation Shock-Wave-Assisted Synthesis

Abstract: Any opinions, findings, and conclusions or recommendations expressed in this publication are those of the author(s) and do not necessarily reflect the views of the Space and Naval Warfare Systems Center (SSC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 51 publications
(108 reference statements)
6
77
0
Order By: Relevance
“…As shown above, several authors [8][9][10][11] reported on coexistence of cubic and hexagonal diamond phases in diamond samples prepared by HPHT and shock wave compression methods, while Nemeth et al reported on defective cubic phase in a meteoritic diamond [13]. Taking into account this diversity of the results and interpretations, we analyze our XRD data within the frameworks of both above-mentioned models, in order to realize which of them better suits our experimental data.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…As shown above, several authors [8][9][10][11] reported on coexistence of cubic and hexagonal diamond phases in diamond samples prepared by HPHT and shock wave compression methods, while Nemeth et al reported on defective cubic phase in a meteoritic diamond [13]. Taking into account this diversity of the results and interpretations, we analyze our XRD data within the frameworks of both above-mentioned models, in order to realize which of them better suits our experimental data.…”
Section: Methodsmentioning
confidence: 84%
“…This phenomenon is often observed in the diamonds prepared by HPHT and shock wave compression methods [8][9][10][11]. Herewith, some authors [8,9,11] reported that the diamond products fabricated by the shock wave synthesis involve both cubic (3C) diamond (space group Fd3m, the lattice constant a ¼ 3.567 Å, Z ¼ 8, C-C bond length 1.544 Å) and hexagonal diamond phases, particularly Lonsdaleite 2H (space group P6 3 /mmc, a ¼ 2.52 A, c ¼ 4.12 A, Z ¼ 4) and 6H polytypes.…”
mentioning
confidence: 99%
“…Recent work shows this technique permits to confirm the tetrahedral insertion of boron atoms in diamond leading to p-doping [61,62]. EELS combined with scanning TEM (STEM) can even provide mapping or profiles of impurities with an atomic resolution [63][64][65]. Near-edge X-ray absorption fine structure (NEXAFS) technique could probe the local bonding environment [66].…”
Section: Diamond Corementioning
confidence: 99%
“…Formation of an organized molecular film of organo-modified nanodiamond was also confirmed by Laser Raman spectroscopy. A diamond-specific 1330 cm -1 Raman shift band 10 was confirmed in the Raman spectrum of the organized film, in addition to the C-C band at 1098 cm -1 . In a nutshell, it was not possible to obtain a quite homogeneous single particle film at this stage.…”
Section: Resultsmentioning
confidence: 69%